Telecommunication companies’ tales to strengthen brand: analysis of television spots during pandemic confinement - Dettleff Pallete, James Anthony (2022)
The mandatory lockdown in Peru, which lasted over three months, made the telecommunication companies redefine their strategies to face the pandemic. This Project analyzes the TV spots of the three main telecommunication companies in Peru to identify their narratives, how they faced the pandemic, the audiovisual resources they had to use, and how they turned to social advertising to strengthen their brands. We worked with an analysis matrix and semi-structured interviews with marketing managers to contrast our main findings. The priority for these companies was to answer to the emergency by guaranteeing connection, which was in line with their Brand purpose, based mainly on emotional speeches and positioning themselves as solutions for their clients during the pandemic scenario. We conclude that the narratives were used as social advertising tools to strengthen brand equity, but mainly targeting their own clients.